MANAJEMEN KONFLIK PENGADAAN TANAH PEMBANGUNAN JALAN TOL PADANG-SICINCIN - Miftah Urrahmi; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research aims to examine the conflict management of land acquisition for the construction of the Padang-Sicincin toll road. The approach used is this research approach using a descriptive qualitative type approach that is gathering information from various sources and can be proven by facts and using documentation studies. From this research it can be seen that the Padang-Sicincin toll road conflict still occurs and is felt by various layers to the lower layers of the community. From the interview results it is known that the conflict management of land acquisition for the construction of the Padang-Sicincin toll road is not yet optimal and an in-depth study is needed. Conflict over toll road development is not only seen from land issues, but many impacts are caused by economic, social and environmental aspects.